A review on heat transfer enhancement in a heat exchanger - Gobinathan, Sashwin Nair; Azizuddin, Abd Aziz; Oumer, Ahmed Nurye; Mohd Yusof, Taib; Ahmad Basirul Subha, Alias (Semarak Ilmu Sdn. Bhd., 2024)
Compact heat exchanger is commonly used in car radiators which is normally small with low flowrate. To produce a large surface area, thin plates or corrugated fins are attached closely separating the two fluids. Compact heat exchanger is normally used in applications where weight and volume are the significant factors for the enhancement of heat transfer. This paper reviews the research related to the characteristics, advantages and findings on various type of compact heat exchanger. It is found that the geometric parameters such as fin shape, tube shape, fin pitch, tube pitch, tube arrangement, tube angle and vortex generators affect the heat transfer performance in general. The air inlet angle of 45° and common flow upstream gives the optimum heat enhancement in most studies while the most suitable air flow is between 1.8 – 3.8 m/s.